Physicians' drug prescribing patterns at the national health insurance scheme unit of a teaching hospital in the North Eastern Nigeria - Roland Nnaemeka Okoro; Barnabas Galadima Shekari (Archives of Global Professionals, 2013)
Objectives: The aims of the present study were to assess the drug prescribing patterns and rational use of drugs. Materials and Methods: Data were collected through a retrospective method between January and March 2012. The out-patient prescription sheets of 12 months period of 2009 were randomly sampled and assessed using WHO prescribing indicators. Results: The average number of drugs per encounter was 3.4 ± 1.4; percentage of drugs prescribed by generic names and percentage of drugs prescribed from NHIS essential drug list were 51.5% and 67.1%, respectively. Percentage of encounters with an antibiotic prescribed and percentage of encounter with an injection prescribed were 56.2% and 5.7%, respectively. The frequency distribution of the commonly prescribed drugs showed that antibiotics, analgesics, and vitamins/minerals were the most frequently prescribed classes of drugs. Conclusion: On one hand, there was under prescribing of injection which is commendable. On the other hand, despite the efforts of WHO and other international organizations in promoting rational use of drugs, irrational prescribing still occurs. There were high tendency of poly pharmacy, overprescribing of antibiotics, lack of compliance with the principles of NHIS essential drugs, and generic prescribing.